2023
DOI: 10.1007/s40894-023-00228-6
|View full text |Cite
|
Sign up to set email alerts
|

Sociodemographic Predictors and Moderators of Treatment Outcomes of Psychotherapeutic Interventions for Young People with Mental Disorders: A Systematic Review

Vera Gergov,
Tamara Prevendar,
Eleni Vousoura
et al.

Abstract: Despite the worrying prevalence of mental disorders among adolescents and young people, evidence on predictors of treatment outcome remains scarce. Systematic reviews have focused on specific disorders or treatment modalities and have not targeted this age group in particular. This systematic review presents an overview of the sociodemographic predictors and moderators on the outcome of psychotherapeutic interventions for adolescents and young people with mental disorders across treatment modalities. The searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 97 publications
0
1
0
Order By: Relevance
“…Several patient factors (c), too, have been demonstrated to predict treatment outcomes, including age, gender, ethnicity, partnership status, comorbidity, self-reported disability, and personality disorder traits, among others (17,19,34). While Luborsky et al's early literature review (1971) (35) suggested better outcomes when therapist and patient genders align, Flückiger et al's (2018) above-mentioned meta-analytic synthesis on the alliance in adult psychotherapy (28) concluded that individual patient characteristics, including gender, generally have a small impact on treatment outcomes compared to other factors, such as the therapeutic alliance.…”
Section: Introductionmentioning
confidence: 99%
“…Several patient factors (c), too, have been demonstrated to predict treatment outcomes, including age, gender, ethnicity, partnership status, comorbidity, self-reported disability, and personality disorder traits, among others (17,19,34). While Luborsky et al's early literature review (1971) (35) suggested better outcomes when therapist and patient genders align, Flückiger et al's (2018) above-mentioned meta-analytic synthesis on the alliance in adult psychotherapy (28) concluded that individual patient characteristics, including gender, generally have a small impact on treatment outcomes compared to other factors, such as the therapeutic alliance.…”
Section: Introductionmentioning
confidence: 99%